A numerical study on nearshore behavior of Japan Sea tsunamis using Green's functions for Gaussian sources based on linear Boussinesq theory. Issue 2 (3rd April 2019) - Yamanaka, Yusuke; Sato, Shinji; Shimozono, Takenori; Tajima, Yoshimitsu
ABSTRACT: The aim of this study is to estimate how and what kinds of tsunamis are generated near shorelines in the Japan Sea, using earthquake tsunami sources proposed by the Japanese government. Tsunami propagation based on these sources was first simulated based on the linear Boussinesq theory for Miho Bay, where a historical tsunami inundated the shoreline. The results indicate that tsunami sources not only near the bay but also farther from the bay could generate significant tsunami fluctuations. Thus, the amplification of the latter tsunamis was examined using Fourier analysis. Tsunami waveforms in the bay periodically fluctuate with large amplitudes after the first wave. The Fourier analysis specified these periods to be 13–16 min, consistent with the estimated resonance periods of the bay. Therefore, it can be concluded that one of the factors responsible for the amplification of tsunamis in Miho Bay is the bay-scale resonance. To investigate why resonance occurs during tsunamis, a relationship between the tsunami source geometry and the generated tsunami was examined. This analysis indicates that specific tsunami sources located in critical areas could enhance the resonance in Miho Bay.